Tungsten oxide as electrocatalyst for improved power generation and wastewater treatment in microbial fuel cell. Issue 19 (23rd August 2020) - Das, Sovik; Ghangrekar, M.M.
ABSTRACT: Microbial fuel cell (MFC) is a device that oxidizes the organic matter present in wastewater and simultaneously generates electricity from it. For practical applications, the power production of MFCs needs to be enhanced and the use of novel anode and cathode catalyst can certainly help in this regard. Such a novel catalyst, WO3, was explored as both anode and cathode catalyst in this study. Performance of MFCs was enhanced when WO3 was used as an electrocatalyst. The maximum power density of MFC was increased by five times when WO3 was used as anode catalyst and by four times when it was used as cathode catalyst as compared to control MFC using electrode without any catalyst. Almost six times increment in maximum power production of MFC was observed when WO3 was used as catalyst on both the electrodes. Electrochemical analysis of WO3 also proved that it could enhance the current density of the modified electrode owing to its electrochemical catalytic properties. Furthermore, chemical oxygen demand (COD) removal of MFC having WO3 coated electrodes was also observed to be higher, thus suggesting an overall enhancement in the performance of MFC by the use of WO3 as an electrocatalyst. GRAPHICAL ABSTRACT: